Being a Good Friend Doesn’t Mean You can Become a Good Therapist - Nistor, Mihai (New Trends in Psychology, 2023)
Many people go with the instinctive thought of becoming therapists to heal themselves, which is good on the one hand, but not optimal for the professional environment on the other. If I’ve found that I’m a good friend, how do I know that I can also become a good therapist? Starting from this question there are a few things to consider before we hit the road. To practice therapy is not to study aspects that you personally like and then apply them to clients, expecting to get great results, plus at some point it can reach the height of insanity “to do the same, expecting different results”, and it is not indicated, because each person is completely different, comes with different requests, and therapists have to adapt.